Tradisi Upacara Adat Tiwah bagi Masyarakat Adat Dayak Ngaju: Studi Kasus di Desa Pujon Provinsi Kalimantan Tengah - Yuni Mariati; Yandi Saputera; Muhammad Mahendra; Fakhruddin Razy (Pusat Riset dan Inovasi Nasional, 2026)
This study aims to identify and analyze customary and criminal sanctions imposed on individuals who violate Hinting Pali during the Tiwah ceremony, as well as the legal and customary consequences for those engaged in gambling within the ritual process. The research employs an empirical approach with a qualitative descriptive method through interviews, observations, and document analysis. The focus of this study is the implementation of Dayak Ngaju customary law in addressing violations that occur during the Tiwah ceremony. The findings reveal that Dayak Ngaju customary law plays a crucial role in maintaining social and spiritual harmony by enforcing moral, social, and symbolic sanctions. Furthermore, there is a point of convergence between customary law and national criminal law in promoting justice and social order. This study is expected to contribute academically to the development of customary law in Indonesia and serve as a valuable reference for communities, scholars, and policymakers in preserving cultural values and ensuring fair law enforcement within the framework of local wisdom.